PENGARUH KONSENTRASI LARUTAN EKSTRAK DAUN LIDAH MERTUA TERHADAP ABSORBANSI DAN TRANSMITANSI PADA LAPISAN TIPIS - Sunardi Sunardi; Kartika Sari (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2012)
It has done research on the effect of the extract solution concentration in-law tongue (Sansevieriatrifasciata) on the absorbance and transmittance in thin layers. Experimental research is that by extracting the leaves of the tongue-in-law to obtain a dye. Then made a solution with a concentration of 1%, 2%, 3%, 4%, 5%, 6% and7%, and also made merua pure aloe extract solution, a solution of TiO 2, and a mixture of both. Characterization of a solution made with UV-Vis spectrometer 1800 which aims to determine the value of absorbance and transmittance. Spectrometer set at a wavelength of 411nm- 665 nm and an absorbance range 0-3. The results show that there is a relationship between the concentration of the absorbance by the equation A = 22,9c + 0.1946. The greater the concentration used, the greater the smaller the value of absorbance and transmittance values. The maximum absorbance obtained at a wavelength Î» = 411 nm and Î» = 665 nm while the absorbance value and the maximum trasmitansi respectively 3,58 and 1,433. . Key words:leaf extract in-law tongue (Sansevieriatrifasciata), absorbance, transmittance.